Quantum effects in multilayer Si-Ge nanoheterostructures - Kozyrev, Yu.N.; Rubezhanska, M.Yu.; Sushyі, A.V.; Kondratenko, S.V.; Vakulenko, O.V.; Dadykin, A.A.; Naumovets, A.G. (Поверхность, 2008)
The lateral photoconductivity spectra and photofield electron emission were used to investigate multilayer Ge/Si heterostructures with Ge quantum dots. Earlier we have revealed a close connection between elastic strain in Ge quantum dots originating due to the lattice mismatch during the epitaxial growth and additional energy level forming in the strained Si-Ge heterojunction region. Thus, it appeared to be possible observing intraband transitions in Ge quantum dots that are absent in two-dimensional Si-Ge heterostructures using such simple and informative methods. While an influence of the number of Ge quantum dot layers on lateral photoconductivity spectra is not essential, the photofield electron emission characteristics showed considerable shift to middle infrared area, as the number of Ge quantum dot layers increased. It was revealed that size and composition parameters of Ge quantum dots correspond to energy levels in the valence band of the latter with the energy distance between them about 0.32 and 0.34 eV with a high accuracy. The results of our investigation make it possible to expect their possible application in new nano- and optoelectronic devices. Методами фотопольової емісії та повздовжньої фотопровідності було досліджено багатошарові наногетероструктури з квантовими точками германію. Попередні дослідження показали тісний зв'язок пружних напружень, що виникають при епітаксійному рості матеріалів з різними постійними граток, з виникненням додаткових рівнів в зоні такого гетеропереходу. Таким чином, відносно простими але інформативними методами спостерігалися міжзонні переходи, які відсутні в двовимірних гетероструктурах Si-Ge. Якщо вплив кількості шарів на фотопольову емісію несуттєвий, то при дослідженні фотопровідності виявлено прямий зв'язок зсуву чутливості повздовжньої фотопровідності в середній інфрачервоний діапазон від кількості шарів з квантовими точками германію. Показано, що розмірні характеристики та мольний склад квантових точок відповідають енергетичним рівням з енергетичною відстанню між ними приблизно 0,32 та 0,34 еВ з дуже високою точністю. Результати досліджень дозволяють сподіватися на їх використання в перспективних приладах нано- та оптоелектроніки.